2020
DOI: 10.1080/21642850.2020.1819287
|View full text |Cite
|
Sign up to set email alerts
|

Why? What? How? Using an Intervention Mapping approach to develop a personalised intervention to improve adherence to photoprotection in patients with Xeroderma Pigmentosum

Abstract: Background: Intervention Mapping (IM) is a systematic approach for developing theory-based interventions across a variety of contexts and settings. This paper describes the development of a complex intervention designed to reduce the dose of ultraviolet radiation (UVR) reaching the face of adults with Xeroderma Pigmentosum (XP), by improving photoprotection. XP is a genetic condition that without extreme UVR photoprotection, leads to high risk of developing skin cancer. Methods: The IM protocol of 6 steps was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Pragmatic repetition of the behaviour in consistent contexts (Lally & Gardner, 2013) may then transfer the behaviour to a habit elicited automatically in the presence of the necessary cues. Indeed, one recent approach to non-adherence to photoprotection in xeroderma pigmentosum included a focus on values within more traditional strategies to facilitate habit formation (e.g., action planning; Walburn et al, 2020). Alongside planning of when and where a specific photoprotection activity would be enacted, participants placed photos of value-related content (e.g., photos of travel destinations aligning with value of being adventurous) next to their photoprotective sunscreen as a visual prompt.…”
Section: Discussionmentioning
confidence: 99%
“…Pragmatic repetition of the behaviour in consistent contexts (Lally & Gardner, 2013) may then transfer the behaviour to a habit elicited automatically in the presence of the necessary cues. Indeed, one recent approach to non-adherence to photoprotection in xeroderma pigmentosum included a focus on values within more traditional strategies to facilitate habit formation (e.g., action planning; Walburn et al, 2020). Alongside planning of when and where a specific photoprotection activity would be enacted, participants placed photos of value-related content (e.g., photos of travel destinations aligning with value of being adventurous) next to their photoprotective sunscreen as a visual prompt.…”
Section: Discussionmentioning
confidence: 99%
“…Using factorial trials to evaluate multiple intervention components, as suggested by the MOST framework, is a relatively new approach in health services research. We made adaptations to IM based on time available and to include important considerations guided by MOST [ 28 , 31 ]. Strengths of our approach include applying an established intervention development method within the MOST framework, and the systematic reporting of the intervention development process.…”
Section: Discussionmentioning
confidence: 99%
“…It consists of six stages that cover designing, implementing and evaluating an intervention, and it promotes relevant stakeholder engagement throughout development [28]. IM has previously been used to develop interventions targeting adherence [29][30][31] and women with breast cancer [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…The XPAND intervention For a full description of the development and content of the XPAND intervention, please refer to our companion paper (Walburn et al, 2020). Briefly, XPAND involved 7, one-toone sessions delivered in person (sessions 1 and 6) or via Skype (sessions 2-5 and 7) by a trained facilitator.…”
Section: Methodsmentioning
confidence: 99%
“…motivation, barriers and facilitators; phase I) that could be targeted to achieve change in the planned intervention (phase II). Outcomes of this formative research (Anderson, Walburn, & Morgan, 2017 ; Anderson, Walburn, & Morgan, 2019 ; Morgan, Anderson, Walburn, Weinman, & Sarkany, 2019 ; Sainsbury et al, 2018b ; Walburn et al, 2019a ; Walburn, Anderson, & Morgan, 2019c ) and the development of the intervention content based on phase I findings (Walburn et al, 2020 ) are reported separately. Briefly, this phase of research resulted in the establishment of 17 evidence statements around which the intervention would be designed and confirmed that, not only did adherence to photoprotection recommendations vary widely, so did the number and pattern of correlates of behaviour, lending further support to the a-priori decision that the planned intervention should be tailored.…”
Section: Introductionmentioning
confidence: 99%